The Relationship Between Body Mass Index and Anemia with Primary Dysmenorrhea in Adolescent Girls - Sari, Septi Indah Permata; Dahlia, Iis (Program Studi Kebidanan Fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Background: Primary dysmenorrhea is menstrual pain that occurs without any organic disorder and is often experienced by adolescent girls. The global prevalence reaches 60–90%, while in Indonesia, approximately 64.25% of adolescents report it. Risk factors include nutritional status (Body Mass Index/BMI) and anemia. An abnormal BMI (either underweight or overweight) is associated with hormonal disorders that can worsen pain, while iron deficiency anemia exacerbates uterine contractions through endometrial tissue hypoxia.Objective : To determine the relationship between BMI and anemia and the incidence of primary dysmenorrhea in adolescent girls.Methods: This study was conducted from January to May 2020 in Babussalam Village, Rokan Hulu Regency. This study was an observational analytic study with a cross-sectional approach. The population in this study were adolescent girls aged 12-16 years in Babussalam Village, Rokan Hulu Regency. Sampling used a total sampling technique of 50 adolescent girls who met the inclusion criteria.Results: The study found that 64.0% of adolescent girls experienced primary dysmenorrhea. Most of the adolescent girls were not anemic (58.0%), and 62.0% had a normal body mass index. The chi-square test analysis with a 95% confidence interval showed a significant relationship between body mass index (p=0.001) and anemia (p=0.003) and the incidence of primary dysmenorrhea in adolescent girls.Conclusion : BMI and anemia are significantly associated with the incidence of primary dysmenorrhea in adolescent girls, with anemia as the most influential factor.Recommendations: Adolescent girls are advised to maintain ideal nutritional status and regularly consume nutritious foods and iron supplements to prevent anemia. Schools and health workers need to increase education on reproductive health, menstrual pain management, and anemia prevention. Further research is recommended, including longitudinal designs and nutritional interventions.Keywords: Adolescents, Body Mass Index (BMI), Anemia, Dysmenorrhea